Rehabilitation Management of Children in Conflict with Law: Trends in India - Das , Pragnya (International Journal of Psychosocial Rehabilitation, 2020)
This paper entails management of rehabilitation of children in conflict with law as prevention strategy to protect the children in conflict from abuse, neglect and exploitation under the Juvenile Justice (Care and Protection) Act, 2015. It covers the institutional and non institutional services provided to children. The purpose of this research is to enhance the legal facilities provided for managing the rehabilitation of children.